Focus Groups to Reveal Parents' Needs for Prenatal Education - Dumas, Louise (The Journal of perinatal education, 2002)
Focus group interviews are a useful qualitative research technique to obtain data from small groups about their opinions, attitudes, and/or feelings on a given subject. This particular technique has been used in Western Quebec in order to reveal the opinions, needs, and feelings of health professionals and future parents concerning prenatal education. As part of the region's priorities for 2002, all future parents in this part of the province were to be offered prenatal, government-paid, community health education. Consequently, the Ministry of Health at the regional level sought a customized program for all community centers, based on identified regional needs and recent research. This program had to prove to be innovative, user-friendly, effective, and efficient. After reviewing the literature and conducting discussions with representatives from all regional health agencies throughout the province, the author of this article designed and conducted focus groups with perinatal health professionals from all community centers and hospitals of the Outaouais region. Later, focus groups were also conducted with parents. Following the analysis of the data and comparisons with existing resources, the author of this paper designed and proposed a specific program aimed at the empowerment of future parents. This paper reports the original problem and its context, the research methodology, and the proposed program (underlying philosophy, objectives, content, and educational techniques).